The Lived Experiences of Migrant Youths at Musina Town in the Limpopo Province of South Africa - Frank, Rapholo Selelo (International Journal of Criminology and Sociology, 2021)
This study sought to explore and describe the lived experiences of migrant youths in South Africa by using Musina as a case study. Several studies reveal that Southern Africa is faced with an increased number of international population movements. Upon their arrival in the host countries, immigrants encounter a vast number of challenges. The new economic theory of migration was used to pursue the aim of this study. This study was qualitative wherein case study and phenomenological designs were triangulated to purposively select 18 migrant youths in Musina. Data was collected through semi-structured interviews and was analysed thematically with the assistance of Nvivo software. Findings reveal that most migrant youths due to problems around documentation are being hated by local citizens and exploited by employers that they end up performing impractical jobs without any benefits and job security. Stigmatisation was also found to be a challenge that migrant youths deal with in South Africa. There should be stringent security at the Beit-Bridge border post to mitigate illegal cross-bordering to South Africa. Integrative programmes should be developed to accommodate legal immigrants into the welfare of South Africa. Immigration laws should have a clause on the monitoring of any job done by immigrants in the host countries. Further research is also recommended in other provinces of South Africa and with significant others such as local citizens and government officials.